Resultive Connectors in Advanced Lithuanian Learners’ English Writing - Bikelienė, Lina (Kalbotyra, 2008)
The importance of the analysis of learner language has long been recognised. The ICLE project has facilitated the research into interlanguage offering reliable data on advanced students’ written work. The Lithuanian subcorpus of ICLE is currently being compiled at Vilnius University. The present paper will report on a pilot study carried out on the material of LICLE on the use of resultive connectors and also will present a brief comparison of the Lithuanian learners’ usage with that of native speakers’ as well as advanced learners’ of other language backgrounds. The central research questions will be the following: • whether advanced Lithuanian learners use English resultive connectors in the same way as native English university students; • whether advanced Lithuanian learners’ usage of English resultive connectors is similar to other non-native learners’; • what possible explanations could be offered.